System Design on Door Locks Using Arduino Based Passwords - Ricky Reyensen Samosir; Jimmie; Meilyana Winda Perdana (Universitas Islam Kuantan Singingi, 2025)
The use of manual locks such as keys, this type of locking is easy to duplicate, prone to loss if taken on a trip and if you forget to close the door, it will provide an opportunity for other people to enter the house or to a private room, for that a door locking device is needed that can provide ease of use from conventional locking, namely using automatic locking using a knock pattern. This research aims to design a door security system. Based on the results of the design and testing of the Arduino-based automatic door locking system using passwords that have been carried out by researchers, it can be concluded that the automatic door locking system using this password can be made and operated using the ATMega328 microcontroller as a control center and circuit and programmed using Arduino IDE software. The Arduino Uno microcontroller can control the automatic door locking working system according to the instruction sequence. The research method used in this research is the field research method. The field research method aims to directly observe the object being studied to obtain the necessary information. System Design and Implementation uses Block Diagram design to describe the activities that exist in the system. In order to know more about the system to be created